2010
DOI: 10.1002/kin.20488
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies on the oxidation of glyoxylic and pyruvic acids by a {Mn3O4}4+ core in aqueous media

Abstract: In aqueous media, the Mn IV trimer [Mn IV 3 (μ-O) 4 (phen) 4 (H 2 O) 2 ] 4+ (1, phen = 1,10phenanthroline) equilibrates with its deprotonated from [Mn 3 (μ-O) 4 (phen) 4 (H 2 O)(OH)] 3+ (2). Among the several synthetic multinuclear oxo-and/or carboxylato-bridged manganese complexes known to date containing metal-bound water, to the best of our knowledge, 1 is one of the rare examples that deprotonates (1 2 + H + ; pK a = 4.00 (±0.15) at 25.0 • C, I = 1.0 mol dm −3 , maintained with NaNO 3 ) at physiological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 150 publications
(40 reference statements)
2
1
0
Order By: Relevance
“…However, proton ambiguity in that case is a serious shortcoming as pointed out by them. The reduction of Mn IV in [Mn IV 3 (µ-O) 4 (Phen)(OH 2 ) 2 ] 4+ by HGl/Gl − have been shown by Mandal and co-workers 24 to follow second order kinetics with the reactivity trend, k red (HGl) > k red (Gl − ), an observation similar to ours but for the proton ambiguity in their case. In a recent study of the oxidation of glyoxylic acid by Mn IV L and Mn III L {L = tetra deprotonated 1,8-bis(2-hydroxybenzamido)-3,6-diazaoctane} Nayak and co-workers 19 have unambiguously demonstrated the higher reactivity of HGl relative to that of its conjugate base, Gl − and attributed this reactivity order to the preferential hydrogen bonding effect of HGl.…”
Section: A B Csupporting
confidence: 88%
See 1 more Smart Citation
“…However, proton ambiguity in that case is a serious shortcoming as pointed out by them. The reduction of Mn IV in [Mn IV 3 (µ-O) 4 (Phen)(OH 2 ) 2 ] 4+ by HGl/Gl − have been shown by Mandal and co-workers 24 to follow second order kinetics with the reactivity trend, k red (HGl) > k red (Gl − ), an observation similar to ours but for the proton ambiguity in their case. In a recent study of the oxidation of glyoxylic acid by Mn IV L and Mn III L {L = tetra deprotonated 1,8-bis(2-hydroxybenzamido)-3,6-diazaoctane} Nayak and co-workers 19 have unambiguously demonstrated the higher reactivity of HGl relative to that of its conjugate base, Gl − and attributed this reactivity order to the preferential hydrogen bonding effect of HGl.…”
Section: A B Csupporting
confidence: 88%
“…This trend is rarely reported in the literature. Interestingly, reduction of Mn IV in [Mn IV 3 (µ-O) 4 (Phen)(OH 2 ) 2 ] 4+ (Phen = 1,10 ortho phenanthroline) by glyoxylate follows a similar trend as reported by Mandal et al 24 , Das et al 25 interpreted the observed increasing trend of k obs with decreasing pH for the reduction of a Mn IV tetramer [Mn 4 (µ-O) 6 (bipy) 6 ] 5+ (bipy = 2,2 bipyridyl) in terms of relatively higher reactivity of the protonated form of the complex with HGl. In another recent study of oxidation of glyoxylic by tris(biguanide)manganese(III) ([(big) 3 Mn III ] 4+ ), Dhar et al 26 report that it is the acid form, HGl, which has kinetic significance in the redox process but not the conjugate anion, Gl − .…”
Section: Equilibrium Measurementssupporting
confidence: 81%
“…[17][18][19][20] Furthermore, the simplicity of the molecule allows modelling the oxidation of organic substrates in the presence of various oxidants. [21][22][23][24][25][26] Pyruvic acid is a simple substrate with a carbonyl group next to a carboxylic group. As such, its oxidation in aqueous solution may yield either acetaldehyde or acetic acid.…”
Section: Introductionmentioning
confidence: 99%